2019
DOI: 10.2147/ott.s189438
|View full text |Cite
|
Sign up to set email alerts
|

<p>First-line tyrosine kinase inhibitors in EGFR mutation-positive non-small-cell lung cancer: a network meta-analysis</p>

Abstract: Background EGFR-tyrosine kinase inhibitors (EGFR-TKIs) including afatinib, dacomitinib, erlotinib, gefitinib, and osimertinib have proven efficacy in terms of progression-free survival (PFS) in patients with non-small-cell lung cancer (NSCLC) harboring EGFR mutations. However, an overall view for comparing efficacy and toxicity on a meta-level is lacking. This study compared efficacy and toxicity of first-line treatment with five different EGFR-TKIs by conducting a network meta-analysis (NMA). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 45 publications
3
46
0
1
Order By: Relevance
“…Although the introduction of EGFR-TKIs into the treatment paradigm for NSCLC improved clinical outcomes for patients ( 4 , 19 ), these agents are associated with several kinds of ADRs, particularly diarrhoea and rash ( 20–22 ). However, a recent network meta-analysis suggested that osimertinib provided an improved benefit-risk profile compared with other EGFR-TKIs ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the introduction of EGFR-TKIs into the treatment paradigm for NSCLC improved clinical outcomes for patients ( 4 , 19 ), these agents are associated with several kinds of ADRs, particularly diarrhoea and rash ( 20–22 ). However, a recent network meta-analysis suggested that osimertinib provided an improved benefit-risk profile compared with other EGFR-TKIs ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Exosomal DNA analysis allows the detection of tumor-specific mutations, which, in the case of heterogeneous solid tumors, can give a more accurate picture of tumor genetics overall than small tissue biopsies [46]. The presence of the mutated epidermal growth factor receptor (EGFR) alleles in exoDNA, especially mutations such as exon 19 Del and exon 21 L858R, characteristic of lung cancer cells, may be important when selecting patients for targeted therapy using a tyrosine kinase inhibitor [40,47]. It has also been shown that mtDNA present in fibroblastderived exosomes activates oxidative phosphorylation (OXPHOS) in breast cancer cells, which leads to resistance to hormone therapy in OXPHOS-dependent breast cancer [48].…”
Section: Composition Of Cancer Exosomesmentioning
confidence: 99%
“…Therefore, a fixed-effect NMA was considered as appropriate. The methods of the NMA are described in more detail in Appendix I and in a previous study [34]. The results of the NMA are presented in Table 1.…”
Section: Systematic Review and Network Meta-analysismentioning
confidence: 99%